Application of Ultrafast Heating and Tempering to Plate Steel - Castro-Cerda, F; Carreño-Saavedra, J (Taylor and Francis Ltd., 2023)
The microstructure and tensile properties were studied in a low-alloy steel plate treated under ultra-fast heating, quenching, and tempering. The microstructure after heat-treatments was predominantly martensite, with low fraction of bainite and ferrite. The tensile tests showed a 100 MPa improvement in strength and a doubling of the total elongation with the increase in heating rate. The tempering process considerably enhanced the ductility from 1–4% to up to 14% in the samples treated at fast heating rates.Furthermore, the work hardening capacity of ultra-fast heated steel was superior compared to steel treated under conventional quenching and tempering. The results suggest that the tempering stage after ultra-fast heat-treatments and quenching further improves the properties compared to the standard quenched and tempered condition. © 2023 Institute of Materials, Minerals and Mining.
Keywords: Steel; microstructure; parent austenite grain size; mechanical properties; ultra-fast heating; tempering